A glimpse of social presence during an organic chemistry group activity - Ballard, Joy; Winfield, Leyte (Frontiers in Education, 2024)
The US must strengthen the STEM workforce to provide solutions that support a resilient society and robust economy. Such solutions require a range of perspectives from individuals with diverse identities. However, women and individuals who identify as a racial or ethnic minority are woefully underrepresented in the STEM workforce. The reality doubly impacts those with intersecting identities, such as Black women. Efforts to increase the representation of Black women in STEM disciplines include interventions that improve their success in undergraduate courses. Paramount to this is expanding understanding of the experiences of Black women in the academic setting.The current work is situated within the social presence of the Community of Inquiry (CoI) framework, examining social talk among Black women in the learning environment. The CoI model holds that the interconnection between teaching, cognitive, and social presences influences how students engage to master course content. More specifically, each presence is critical for the student's ability to connect with their peers and instructor and engage in discourse related to the application of information. The characterization of social presence was captured through audio and visual recordings. The videos were examined for academic and non-academic social talk. Few studies have been done to characterize CoI in academic spaces consisting only of Black women.Disaggregating the stories of Black women from the broader context provides the visibility needed to understand their experiences and imagine a STEM paradigm responsive to their existence. Such knowledge is critical to understanding better how women, particularly women of African descent, navigate the learning environment. The article provides a preliminary look at Black women in an active learning setting to shed light on the experiences of these individuals in the STEM context.